The Effect of Social Support and Academic Resilience on Burnout in Students Working on a Thesis - Oktaviani, Dinda Nur; Rozi, Fahrul (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The objective of this study is to analyze the effect of social support and academic resilience on burnout in students engaged in thesis work. The study involved 324 students engaged in thesis work on the island of Java. This research method employs a quantitative approach. The data processing stage utilizes the Jamovi 2.3 software, which employs multiple linear regression models. The data were collected via an online questionnaire. The results of hypothesis testing indicate that social support has no effect on burnout. Conversely, academic resilience has a positive effect on burnout. Furthermore, social support and academic resilience simultaneously affect burnout by 2.35%, with an F value of 4.89 and a significance value of 0.008 (p<0.05). The findings of this research are of value to the field of education with regard to the topics of social support, academic resilience, and burnout. In particular, this research is of interest to students engaged in thesis work. The update of this research is the population on the island of Java. The results of the study indicated that social support has no effect on burnout. Conversely, the results of the academic resilience research demonstrated a positive influence on burnout.